2021
DOI: 10.1029/2021jd035172
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Raindrop Size Distributions in Chongqing Observed by a Dense Network of Disdrometers

Abstract: This study investigates the characteristics of raindrop size distribution (RSD) including the temporal and spatial variabilities and the summer rain RSD features using 34 Parsivel disdrometers data from Jan. 2015 to Jan. 2016 in Chongqing, an inland municipality in Southwest China. The observed RSDs are fitted with the gamma distribution (N(D) = N0Dμe−λD) in this study. Rainfall in summer differs greatly from winter with larger rain rate, rain water content and variabilities. From winter to summer, raindrop si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 79 publications
(180 reference statements)
0
1
0
Order By: Relevance
“…Using nine months of DSD observations from ten disdrometers, Han et al [26] showed that Beijing, located in north China, had lower D m and N w values compared to south China, which they attributed to the influence of terrain. Liu et al [27] studied the temporal and spatial variabilities utilizing 34 disdrometers over a two-year period in southwest China, and found significantly different DSD characteristics and parameter relationships between southwest China and other regions such as north, eastern and southern China. Based on use of a disdrometer over four months, Wu et al [28] observed that the number concentration for larger raindrops in southern China exceeded that of the Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…Using nine months of DSD observations from ten disdrometers, Han et al [26] showed that Beijing, located in north China, had lower D m and N w values compared to south China, which they attributed to the influence of terrain. Liu et al [27] studied the temporal and spatial variabilities utilizing 34 disdrometers over a two-year period in southwest China, and found significantly different DSD characteristics and parameter relationships between southwest China and other regions such as north, eastern and southern China. Based on use of a disdrometer over four months, Wu et al [28] observed that the number concentration for larger raindrops in southern China exceeded that of the Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%